Niche partitioning on Sumatran Elephant (Elephas maximus sumatranus) and human in space and resources in Riau, Indonesia - YOHANES WISNU SUKMANTORO; HADI SUKADI ALIKODRA; AGUS PRIJONO KARTONO; EFRANSJAH EFRANSJAH (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Sukmantoro YW, Alikodra HS, Kartono AP, Efransjah. 2019. Niche partitioning on Sumatran Elephant (Elephas maximus sumatranus) and human in space and resources in Riau, Indonesia. Biodiversitas 20: 1362-1373. Research on elephant and human niches at Balai Raja and Tesso Nilo have been done for 6 years (2012-2017). The study was conducted by recording the distribution of elephants and communities. The distribution of elephants was identified through an installed GPS Collar in 3 groups of elephants (Butet, Angelina and Desma) since 2012. In 2016, data collection of resources was done through OLI 8+ Landsat imagery and records from the field. From the results of the study, elephants (Desma, Angelina and Butet groups) and humans have significantly different niches in space, but in terms of resources, all three elephant groups are almost the same to use them. In the context of niche partitioning of resources, Desma group used more thenatural forest, swamp and wasteland areas than the communities. InTesso Nilo, elephants groups used more open land than the communities.The overlapping between elephant and human creates human-elephant conflicts. For this reason, strengthening the niche partitioning strategy in space and resources can be a solution to conflict reduction. In addition, if elephants with humans are forced to live in the same space and resources, they develop strategies of neutralism or coexistence. For the community, converting plant commodities in the direction of an elephant's dislike (still of economic value) can reduce losses for the community and create a non-disturbing relationship between elephant and human. Examples of what the community has done are cassava cultivation and timber industry concession strategy in planting Acacia which is relatively not detrimental to the company even though the plant is damaged by an elephant.